Best practices for the management of thymic epithelial tumors: A position paper by the Italian collaborative group for ThYmic MalignanciEs (TYME). (December 2018) - ,; Alloisio, Marco; Apolone, Giovanni; Ardizzoni, Andrea; Benvenuti, Mauro; Berruti, Alfredo; Breda, Cristiano; Buzzoni, Carlotta; Calabrese, Fiorella; Caraceni, Augusto; Cardillo, Giuseppe; Casadio, Caterina; et al.
Highlights: TETs are rare and heterogeneous tumors with complex multidisciplinary management. Although guidelines are available there is inhomogeneity in their treatment. Experts from Italian centres convened a first meeting to discuss controversies. The paper summarizes the results and provides treatment recommendations. Abstract: Thymic epithelial tumors (TETs) are a heterogenous group of rare tumors, with a complex histopatological classification. Furthermore, the recent introduction of the first TNM staging system, that is scheduled to replace the Masaoka-Koga system, may create further difficulties in TET management, that remains challenging. Several guidelines for treatment of TETs are available and provide recommendations based mainly on non randomized trials and retrospective or limited series. Often the lack of evidence leads to formulation of indications based on expert opinions. As for other rare cancers it is crucial to create networks to coordinate the work among centres involved in treatment of these diseases in order to offer the best diagnostic and therapeutic tools. For this purpose, in 2014 a network named TYME (ThYmic MalignanciEs), was founded in Italy with the aim of improving care and research in TETs. In September 2017 a panel of multidisciplinary experts from TYME network and from other Italian centres strongly involved in TET diagnosis and treatment convened a first Italian Expert meeting together with representatives of association for patients affected by rare thoracic cancers Tu.To.R, to explore how these tumors are managed in the different centres of Italy compared to ESMO guidelines. In this paper we summarize the issues discussed during that meeting and we propose recommandations based on Masaoka Koga and the new TNM staging system.